FORMATION OF CREATIVE PERSONALITY: AXIOM LIFE SUCCESS - Rozman, Iryna (Mountain School of Ukrainian Carpaty, 2022)
The article reveals the essence and importance of forming a creative personality since studying in secondary education. It is noted that dynamic changes in all spheres of human activity serve the need to form a high level of intellectual development of the individual. It is emphasized that human creativity is capable of creating and mastering innovations in any field. Modern trends in society have every opportunity to educate the critical generation. It is noted that the young man at the moment is not only an observer, but the creator of his own happiness. Young people are able to generate original ideas, take on solutions to bold ideas, non-standard solutions, be responsible for them. The aim of the article is to analyze the studied forms of work on the development of creative personality and to offer their own conclusions before the implementation of a successful own life position. The study of these issues was both general and special methods of studying issues: research and study of the material used, abstraction, coincidence from the abstract to the personal level. It is indicated on the results of research, which are confirmed by their own arguments about the importance of forming flexible qualities for development and creative personality. To address this issue, it is necessary to take into account promising educational technologies. They form the essence of the methodological culture of the future specialist. The formation of a creative personality should take place in the process of professional training of future teachers. This approach determines the direction of professional and pedagogical activities, which contributes not only to the development but also to the further self-development of the professional teacher. It is emphasized that the creative personality is a type of personality, which is characterized by a stable, high level of creativity, motivational and creative activity. These qualities are manifested in organic unity with a high level of creativity. These abilities allow individuals to achieve progressive, socially and personally significant results in one or more activities. Scholars distinguish the following traits of creative personality: problematic vision of the situation, boldness of thought, flexibility of thinking, alternative, independence, dialectics, tolerability and critical thinking. Analyzing the opinions and conclusions of well-known experts, it is proved that the creative abilities of the individual – a combination of personal qualities and character traits in accordance with the requirements of a particular type of educational and creative activities. Keywords: critical-thinking generation, creative thought, driving force, creative approach, human capital, innovative type, methodical thinking, self-development.